ISSUES AND CHALLENGES IN THE IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT: BASES FOR POLICY RECOMMENDATION - Eleanor A. Osea (PT. BATARI EDU CALYA, 2023)
This study focused on the issues and challenges met by the School- Based Management (SBM) Team of the six schools within Albay and Camarines Sur. With the use of a survey-questionnaire distributed to the 48 respondents, it was found out that the issues encountered by the SBM Team include the availability, authenticity, and veracity of documents. On the other hand, the most significant challenge lies in the appreciation of documents by the validating team. Overall, the issues determined in this study are feasible. The continuous and improved cooperation of all stakeholders is deemed essential to establish an Advanced SBM Level of Practice.